The Effects of Fetal Gender on Maternal and Fetal Insulin Resistance - Walsh, Jennifer M. (PLoS One, 2015)
OBJECTIVE: Gender plays a role in the development of a number of cardiovascular and metabolic diseases and it has been suggested that females may be more insulin resistant in utero. We sought to assess the relationship between infant gender and insulin resistance in a large pregnancy cohort. STUDY DESIGN: This is a secondary analysis of a cohort from the ROLO randomized control trial of low GI diet in pregnancy. Serum insulin, glucose and leptin were measured in early pregnancy and at 28 weeks. At delivery cord blood C-peptide and leptin were measured. A comparison of maternal factors, fetal biometry, insulin resistance and leptin was made between male and female offspring. A multivariate regression model was built to account for the possible effects of maternal BMI, birthweight and original study group assignment on findings. RESULTS: A total of 582 women were included in this secondary analysis, of whom 304 (52.2%) gave birth to male and 278 (47.8%) gave birth to female infants. Compared to male infants at birth, female infants were significantly lighter, (3945 ± 436 vs. 4081± 549g, p<0.001), shorter in length (52.36 ± 2.3 vs. 53.05 ± 2.4cm, p<0.001) and with smaller head circumferences (35.36 ± 1.5 vs. 36.10 ± 1.1cm, p<0.001) than males. On multiple regression analysis, women pregnant with female fetuses were less insulin resistant in early pregnancy, i.e. had lower HOMA indices (B = -0.19, p = 0.01). Additionally female fetuses had higher concentrations of both cord blood leptin and C-peptide at birth when compared to male offspring (B = 0.38, p<0.001 and B = 0.31, p = 0.03 respectively). CONCLUSION: These findings suggest gender is a risk factor for insulin resistance in–utero. Additionally, carrying a female fetus decreases the risk of insulin resistance in the mother, from as early as the first trimester.